Cultural interpretation of e-commerce acceptance in developing countries: Empirical evidence from Malaysia and Algeria - Zakariya Belkhamza; Syed Azizi Wafa Syed Khalid Wafa (IGI Global, 2008)
Global deployment in information and communication technology requires understandings of the cultural constraints in technology acceptance and usage behavior. Prior research indicates that the salient technology acceptance models may not be applicable to all cultures since empirical support was mainly obtained from North America and developed countries. There has been little research done on technology acceptance and usage behavior in the context of developing countries which exhibit distinctive cultural differences from developed countries. The purpose of this study is to test the cross-cultural applicability of technology acceptance model in two developing countries, Malaysia and Algeria, and to investigate the influence of cultural values on the acceptance of e-commerce. The four cultural values of individual-ism/collectivism, power distance, uncertainty avoidance, and masculinity/femininity identified by Hofstede are posited to comparatively explain the e-commerce acceptance in the context of the two countries. Only uncertainty avoidance was found to moderate the relationship between perceived usefulness and intention to use e-commerce, whereas the other three national culture dimensions did not moderate the relationship, which validate the longstanding notion of important cultural differences between Malaysia and Algeria and show that those differences extend to the e-commerce context.